Diastereospecific Enantiodivergent Allylation of Pyrazolones as an Entry to β‐Aminoamides. Issue 19 (22nd April 2022) - Wannenmacher, Nick; Heberle, Martin; Yu, Xin; Demircan, Aysegül; Wanner, Daniel M.; Pfeffer, Camilla; Peters, René
Abstract: A diastereospecific enantiodivergent allylation of pyrazolones is reported which is catalyzed by a planar chiral pentaphenylferrocene based palladacycle. With the same catalyst batch both product enantiomers were selectively available. The method is applicable to structurally diverse substrates and gave products with enantiomeric excesses between 85 and 94%. In addition, we could show that pyrazolones are transformable into β‐aminoamides. Abstract :